KINERJA KEPALA DESA DALAM PELAKSANAAN PEMBANGUNAN DI DESA TEMPOK KECAMATAN TOMPASO KABUPATEN MINAHASA - SINGAL, SILVIA; TAMPI, GUSTAAF BUDDY; PLANGITEN, NOVVA (Sam Ratulangi University, 2019)
This study uses the title of the village head in the implementation ofdevelopment in the village of Tempok, Tompaso District. The focus of this studyuses the theory of performance according to Gomes (2003: 134) suggests fourindicators in measuring performance. This study used a qualitative method,informants of this study were 10 people taken from the Village Head, VillageSecretary, Village Head, Head of Development, Chair of the Village ConsultativeBody, community members. Data collection uses interview, collection andarrangement techniques. the data analysis technique used in this qualitativeresearch method is inductive proposed by Sugiyono. The results of this study areseen from 4 indicators, namely: (1) the work of the village head has been verygood can be seen from the success of several implementation of development inaccordance with community needs. (2) the quality of work in the implementationof development is quite good, it can be seen from the village head, as well as theliberation and direction of the village consultative body (BPD) and villageofficials. (3) the work knowledge of the village head is good in the eyes of thecommunity because the village head is able to realize the development policies inaccordance with what is needed by the community. (4) the cooperation of thevillage head is very good in the implementation of tasks can be seen from eachprocess of carrying out the work, the village head always tries to move thecommunity to work together to carry out the process of implementation of villagedevelopment.Keywords : Village, Head Performance, Development.